A high-contrast polyetheretherketone material that meets aviation standards and a preparation method thereof

By introducing printing additives with specific particle size and morphology in the polyether ether ketone synthesis process, a high-contrast polyether ether ketone material that meets the requirements of aviation standards has been successfully developed, which has solved the insufficient contrast of UV laser marking in the prior art. Problem, efficient and durable UV marking is achieved.

CN118878815BActive Publication Date: 2025-02-11江苏君华特种高分子材料股份有限公司 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411108483.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-02-11
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

The prior art cannot provide high-contrast polyether ether ketone materials that meet aviation standards, especially when marking less than 55% when marking UV lasers.

Method used

Polyether ether ketone material with high contrast was prepared by mixing the labeling additive with difluorobenzone compound, a rekinetone compound, a salt forming agent and a reaction solvent, and conducting salt forming reaction and in-situ polymerization.

Benefits of technology

The obtained polyether ether ketone material has a high contrast ratio of at least 55% when labeled at UV laser, fully meeting the contrast requirements in aviation standard SAE AS22759A, while simplifying the production process and reducing waste of energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118878815B_ABST
    Figure CN118878815B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polyetheretherketone materials, and in particular to a high-contrast polyetheretherketone material meeting the requirements of aviation standards and a preparation method thereof, comprising the following steps: uniformly mixing a marking auxiliary agent with a difluorobenzophenone compound, a hydroquinone compound, a salt-forming agent and a reaction solvent to firstly perform a salt-forming reaction, and then perform in-situ polymerization to obtain a high-contrast polyetheretherketone material meeting the requirements of aviation standards; wherein the marking auxiliary agent is a compound of a flaky filler and a spherical filler, and the median particle size of the marking auxiliary agent is less than 0.5 μm; the high-contrast polyetheretherketone material of the invention has a UV laser marking contrast of at least 55% on its surface, which can meet the requirements of aerospace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyetheretherketone materials, and in particular to a high-contrast polyetheretherketone material that meets aviation standard requirements and a preparation method thereof. Background Art

[0002] As a special engineering plastic, polyetheretherketone has the characteristics of high heat resistance, chemical corrosion resistance, wear resistance, fatigue resistance, hydrolysis resistance and excellent electrical properties. It has been widely used in various fields such as aerospace, electronics and electrical, analytical instruments, biomedicine, new energy, etc. and has become an indispensable key material.

[0003] In some complex application scenarios, it is necessary to code and mark the boards, rods and films made of polyetheretherketone to record relevant information of the product such as material type, product model, production batch, etc. The mainstream coding and marking methods on the market are inkjet coding and UV laser coding. Among them, inkjet coding products are prone to fading after long-term use, resulting in blurred markings; while products using UV laser coding have the advantages of high clarity and strong durability and are widely promoted.

[0004] The clarity of UV marking is usually measured by the contrast value. The aviation standard SAE AS22759 requires that when UV laser marking is used, the surface of the finished cable should be laser-markable, and the mark contrast should be at least 55%. However, there is currently no report on high-contrast polyetheretherketone materials that meet the requirements for UV marking. Summary of the invention

[0005] In order to solve the above technical problems, a high contrast polyetheretherketone material meeting the requirements of aviation standards and a preparation method thereof are provided. The polyetheretherketone material obtained by the method of the present invention has a high contrast of at least 55% during UV laser marking, which can meet the requirements of aerospace.

[0006] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:

[0007] A method for preparing a high-contrast polyetheretherketone material that meets aviation standard requirements, comprising the following steps: uniformly mixing a marking aid with a difluorobenzophenone compound, a hydroquinone compound, a salt-forming agent and a reaction solvent to firstly perform a salt-forming reaction, and then perform in-situ polymerization to obtain a high-contrast polyetheretherketone material that meets aviation standard requirements;

[0008] The marking aid is a compound of a flake filler and a spherical filler in a mass ratio of 1:1-3:1, and the median particle size of the marking aid is less than 0.5 μm; based on the obtained high-contrast polyetheretherketone material, the marking aid accounts for 10%-20%.

[0009] Furthermore, the median particle size of the marking aid is no more than 0.3 μm, the flaky filler is selected from one or more of talc, mica powder, ultrafine flaky a-Al2O3 powder, and kaolin, and the spherical filler is selected from one or more of titanium dioxide, silicon dioxide, and clay powder;

[0010] The difluorobenzophenone compound is selected from 4,4-difluorobenzophenone and / or 3,3'-difluorobenzophenone;

[0011] The hydroquinone compound is selected from one or more of hydroquinone, phenyl hydroquinone, o-methyl hydroquinone, tert-butyl hydroquinone, methoxy hydroquinone, 2-isopropyl hydroquinone, 2,6-dimethyl hydroquinone, 2,3-dimethyl hydroquinone, resorcinol, 2-ethyl resorcinol, 4-ethyl resorcinol, 5-pentyl resorcinol, 4-hexyl resorcinol, and 4-isopropyl resorcinol;

[0012] The salt-forming agent is selected from potassium carbonate and / or sodium carbonate, with a water content of less than 0.2% and a purity of greater than 99.9%;

[0013] The reaction solvent is selected from one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone and dimethyl sulfoxide.

[0014] Furthermore, the molar ratio of the difluorobenzophenone compound to the hydroquinone compound is 1-1.1:1; the amount of the salt-forming agent is 50%-60% of the total molar amount of the difluorobenzophenone compound and the hydroquinone compound; and the amount of the reaction solvent is 2.5 to 3 times the total weight of the difluorobenzophenone compound and the hydroquinone compound.

[0015] Furthermore, the overall reaction is carried out under a protective atmosphere; the temperature of the salt-forming reaction is 135-145° C. and the reaction time is 1-3 hours; the temperature of the in-situ polymerization is 190-210° C. and the reaction time is 2-8 hours.

[0016] Furthermore, after the in-situ polymerization is completed, the polymerization temperature is maintained, a small molecular weight diphenol monomer is added to adjust the molecular weight for 0.5-1h, and / or a capping agent is added to cap the monomer for 0.5-1h.

[0017] Furthermore, after the in-situ polymerization is completed, a poor solvent is used to precipitate the product from the system after the reaction, and the product is washed and dried. The poor solvent is usually pure water.

[0018] Another aspect of the present invention provides a high-contrast polyetheretherketone material that meets aviation standards and is obtained by the above-mentioned preparation method, wherein the contrast of the mark after UV laser marking is at least 55%.

[0019] Beneficial technical effects:

[0020] The present invention introduces a printing aid with a specific particle size (D50 is 0.3 μm) and a specific morphology (compound of flaky talc and spherical titanium dioxide) during the synthesis process of polyetheretherketone, and successfully develops a high-contrast polyetheretherketone material with clear and ultra-durable ultraviolet marking, and the contrast C can fully meet the contrast standard requirement of ≥55% in aviation AS22759A; the present invention avoids the subsequent use of twin-screw extrusion blending processing by dispersing a high-reflective filler with a specific particle size in a monomer at the front end of the synthesis, simplifies the production process, and reduces energy waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a physical picture of the contrast of the marks obtained by UV laser marking of the polyetheretherketone materials prepared in Example 1, Comparative Example 2, and Comparative Example 3, and only grayscale processing was performed on the physical picture. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.

[0023] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0024] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.

[0025] The following preparation case takes the preparation of a conventional polyetheretherketone structure as an example. The monomers used to prepare the conventional polyetheretherketone structure are 4,4-difluorobenzophenone and hydroquinone. In order to enrich the structure of polyetheretherketone, technicians in this field can use similar difluorobenzophenone compounds and hydroquinone compounds for polymerization. The selection of specific compounds can be found in the content of the invention, which will not be repeated here.

[0026] Example 1

[0027] A method for preparing a high-contrast polyetheretherketone material that meets aviation standard requirements comprises the following steps:

[0028] Under N2 protection conditions, the materials and amounts of the corresponding cases in Table 1 below (wherein the median particle size of the labeling aid is D50 = 0.3 μm, and the salt-forming agent is sodium carbonate) were added to the stirred reactor in sequence, and the salt-forming reaction was first carried out at 140° C. for 2 h, and then the temperature was raised to 195° C. and an in-situ polymerization reaction was carried out for 6 h;

[0029] The reacted material was poured into anhydrous ethanol for precipitation, the precipitated product was separated and washed (washed with distilled water 6 times), and finally dried under vacuum at 100° C. for 48 hours to obtain a high-contrast polyetheretherketone material that meets aviation standards.

[0030] In this case, the total weight of talc and titanium dioxide accounts for about 14% of the final product.

[0031] Example 2

[0032] A method for preparing a high-contrast polyetheretherketone material that meets aviation standard requirements comprises the following steps:

[0033] Under N2 protection conditions, the materials and amounts of the corresponding cases in Table 1 below were added to the stirred reactor in sequence (wherein the median particle size of the labeling aid D50 = 0.3 μm, and the salt-forming agent was sodium carbonate and potassium carbonate in a molar ratio of 2:1), and the salt-forming reaction was first carried out at 138° C. for 2.5 h, and then the temperature was raised to 200° C. and an in-situ polymerization reaction was carried out for 7 h;

[0034] The reacted material was poured into anhydrous ethanol for precipitation, the precipitated product was separated and washed (washed with distilled water 6 times), and finally dried under vacuum at 100°C for 48 hours to obtain a high-contrast polyetheretherketone material that meets the requirements of aviation standards.

[0035] In this case, the total weight of talc and titanium dioxide accounts for about 12% of the final product.

[0036] Example 3

[0037] A method for preparing a high-contrast polyetheretherketone material that meets aviation standard requirements comprises the following steps:

[0038] Under N2 protection conditions, the materials and amounts of the corresponding cases in Table 1 were added to the stirred reactor in sequence (wherein the median particle size of the labeling aid D50 = 0.3 μm, and the salt-forming agent was sodium carbonate and potassium carbonate in a molar ratio of 2:1), and the salt-forming reaction was first carried out at 143° C. for 1.5 h, and then the temperature was raised to 195° C. and an in-situ polymerization reaction was carried out for 5 h;

[0039] The reacted material was poured into anhydrous ethanol for precipitation, the precipitated product was separated and washed (washed with distilled water 6 times), and finally dried under vacuum at 100°C for 48 hours to obtain a high-contrast polyetheretherketone material that meets the requirements of aviation standards.

[0040] In this case, the total weight of talc and titanium dioxide accounts for about 18% of the final product.

[0041] Comparative Example 1

[0042] The preparation process of the polyetheretherketone material in this case is the same as that in Example 1, except that talcum powder and titanium dioxide are not added. This case is a blank control group.

[0043] Comparative Example 2

[0044] The preparation process of the polyetheretherketone material in this case is the same as that in Example 1, except that only 110 g of titanium dioxide is added.

[0045] Comparative Example 3

[0046] The preparation process of the polyetheretherketone material in this case is the same as that in Example 1, except that only 110 g of talcum powder is added.

[0047] Comparative Example 4

[0048] The preparation process of the polyetheretherketone material in this case is melt blending: weigh 860g of polyetheretherketone matrix material, 140g of titanium dioxide and talcum powder (the powder particle size is the same as in Example 1), mix the two in a high-speed mixer, and then melt-blend and extrude them in a twin-screw extruder with a melting temperature of 360-380°C.

[0049] Comparative Example 5

[0050] The preparation process of the polyetheretherketone material in this case is the same as that in Example 1, except that the median particle size of the titanium dioxide and talcum powder is D50=3 μm.

[0051] Table 1 Material formula of each case of comparative examples 1-3 and embodiments 1-3

[0052]

[0053] The performance of the materials in the above embodiments and comparative examples was tested, and the test results are shown in Table 2.

[0054] The SAE AS22759 standard records the contrast test method: illuminate the sample at a 45° angle with a certain light source, and then use a photometer to vertically test the backlight intensity of the sample at the coded and uncoded parts. The backlight intensity value at the coded part is recorded as L m , the backlight intensity value of the uncoded area is recorded as L b, substitute the measured value into formula 1 to obtain the corresponding contrast.

[0055] The contrast value is used to measure the clarity of the UV logo. The calculation formula of contrast C is as follows:

[0056]

[0057] The larger the contrast C value, the clearer the UV mark.

[0058] Table 2 Data of each case

[0059]

[0060] As shown in Table 1, the present invention can improve the backlight intensity of the uncoded and unmarked areas (i.e., increase L b Value), thereby significantly improving the contrast C of the product. When the particle size of the printing aid is D50 = 0.3 μm, the smaller the particle size, the greater its volume fraction, so the reflection of light is higher and just meets the half wavelength of visible light, so the reflection of light is also higher, L b The bigger the C, the bigger it is.

[0061] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a high-contrast polyetheretherketone material that meets aviation standards, characterized in that: The method comprises the following steps: uniformly mixing a marking auxiliary agent with a difluorobenzophenone compound, a hydroquinone compound, a salt-forming agent and a reaction solvent to firstly perform a salt-forming reaction, and then perform in-situ polymerization to obtain a high-contrast polyetheretherketone material that meets the requirements of aviation standards; The marking auxiliary agent is a compound of a flake filler and a spherical filler in a mass ratio of 1:1-3:1, and the median particle size of the marking auxiliary agent does not exceed 0.3 μm; based on the obtained high-contrast polyetheretherketone material, the marking auxiliary agent accounts for 10%-20%; The flake filler is selected from talc powder, and the spherical filler is selected from titanium dioxide.

2. The method for preparing a high-contrast polyetheretherketone material that meets aviation standards according to claim 1, characterized in that: The difluorobenzophenone compound is selected from 4,4-difluorobenzophenone and / or 3,3'-difluorobenzophenone; The hydroquinone compound is selected from one or more of hydroquinone, phenyl hydroquinone, o-methyl hydroquinone, tert-butyl hydroquinone, methoxy hydroquinone, 2-isopropyl hydroquinone, 2,6-dimethyl hydroquinone, 2,3-dimethyl hydroquinone, resorcinol, 2-ethyl resorcinol, 4-ethyl resorcinol, 5-pentyl resorcinol, 4-hexyl resorcinol, and 4-isopropyl resorcinol; The salt-forming agent is selected from potassium carbonate and / or sodium carbonate, with a water content of less than 0.2% and a purity of greater than 99.9%; The reaction solvent is selected from N-methyl-2-pyrrolidone.

3. The method for preparing a high-contrast polyetheretherketone material that meets aviation standards according to claim 2, characterized in that: The molar ratio of the difluorobenzophenone compound to the hydroquinone compound is 1-1.1:1; the amount of the salt-forming agent is 50%-60% of the total molar amount of the difluorobenzophenone compound and the hydroquinone compound; the amount of the reaction solvent is 2.5 to 3 times the total weight of the difluorobenzophenone compound and the hydroquinone compound.

4. A method for preparing a high-contrast polyetheretherketone material that meets aviation standards according to any one of claims 1 to 3, characterized in that: The overall reaction is carried out under a protective atmosphere; the temperature of the salt-forming reaction is 135-145° C., and the reaction time is 1-3 hours; the temperature of the in-situ polymerization is 190-210° C., and the reaction time is 2-8 hours.

5. The method for preparing a high-contrast polyetheretherketone material that meets aviation standards according to claim 4, characterized in that: After the in-situ polymerization is completed, the polymerization temperature is maintained, a small molecular weight diphenol monomer is added to adjust the molecular weight for 0.5-1h, and / or a capping agent is added to cap for 0.5-1h.

6. The method for preparing a high-contrast polyetheretherketone material that meets aviation standards according to claim 4, characterized in that: After the in-situ polymerization is completed, a poor solvent is used to precipitate the product from the system after the reaction, and the product is washed and dried.

7. The high-contrast polyetheretherketone material meeting the requirements of aviation standards obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The high-contrast polyetheretherketone material has a UV laser marking contrast of at least 55% on its surface.

Citation Information

Patent Citations

  • Preparation method and application of low-VOC (volatile organic compound) polyether-ether-ketone

    CN116253871A